1994
DOI: 10.1108/02634509410065555
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks and Statistical Techniques in Marketing Research

Abstract: Outlines the differences and similarities between the two techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Nguyen and Cripps (2001) compared the predictive performance of ANN and MRA for single family housing sales and found that ANN performed better than MRA when a moderate to large data sample size was used. Venugopal and Baets (1994) conducted a conceptual comparison of ANN and statistical techniques such as regression analysis, discriminant analysis, cluster analysis and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen and Cripps (2001) compared the predictive performance of ANN and MRA for single family housing sales and found that ANN performed better than MRA when a moderate to large data sample size was used. Venugopal and Baets (1994) conducted a conceptual comparison of ANN and statistical techniques such as regression analysis, discriminant analysis, cluster analysis and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Number of areas such as manufacturing, marketing, and retailing used it [16]. Several authors have given comprehensive reviews of neural networks, examples of its applications, and comparisons with the statistical approach [11], [17].…”
Section: Neural Networkmentioning
confidence: 99%
“…The artificial neural network model, inspired by the structure of the nerve cells in the brain, can be represented as a massive parallel interconnection of many simple computational units interacting across weighted connections [21] . Each computational unit (or neuron or node) consists of a set of input connections that receive signals from other computational units, a set of weights for input connection and a transfer function (Fig.…”
Section: Multi-layer Feed-forward Neural Network (Mlfn)mentioning
confidence: 99%